Interagency collaborative care for young people with complex needs: Front‐line staff perspectives. (25th February 2019) - Morgan, Sonya; Pullon, Susan; Garrett, Susan; McKinlay, Eileen
Abstract: Worldwide, a growing burden of health and social issues now affect young people. Interagency collaboration and the "integration" of health and social care services are advocated to address the increasingly complex needs of at‐risk youth and to reduce barriers to accessing care. In New Zealand, Youth‐One‐Stop‐Shops (YOSSs) provide integrated health and social care to young people with complex needs. Little is known about how YOSSs facilitate collaborative care. This study explored the collaboration between YOSSs and external agencies between 2015 and 2017 using a multiple case study method. This paper reports qualitative focus group and individual interview data from two of four case sites including six YOSS staff and 14 external agency staff. Results showed participants regarded collaboration as critical to the successful care of high needs young people and were positive about working together. They believed YOSSs provided effective wraparound collaborative care and actively facilitated communication between diverse agencies on behalf of young people. The main challenges participants faced when working together related to the different "world views" and cultures of agencies which can run contrary to collaborative practice. Despite this, some highly collaborative relationships were apparent and staff in the different agencies perceived YOSSs had a lead role in co‐ordinating collaborative care and were genuinely valued and trusted. However without the YOSS involvement, collaboration between agencies in relation to young people was less frequent and rarely went beyond limited information exchange. Establishing and maintaining trusting interpersonal relationships with individual staff was key to successfully negotiating agency differences. The study confirms that collaboration when caring for young people with high needs is complex and challenging, yet agencies from diverse sectors value collaboration and see the YOSS integrated wraparound approach as an important model of care.